2021
DOI: 10.1055/a-1293-7279
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield of endoscopic ultrasound-guided tissue acquisition in autoimmune pancreatitis: a systematic review and meta-analysis

Abstract: Background and study aims There is limited evidence on the diagnostic performance of endoscopic ultrasound (EUS)-guided tissue acquisition in autoimmune pancreatitis (AIP). The aim of this meta-analysis was to provide a pooled estimate of the diagnostic performance of EUS-guided fine-needle aspiration (FNA) and fine-needle biopsy (FNB) in patients with AIP. Patients and methods Computerized bibliographic search was performed through January 2020. Pooled effects were calculated using a random-effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
(72 reference statements)
0
18
0
Order By: Relevance
“…In recent years, new FNB needles have been developed to maintain tissue architecture in samples [37]. These needles showed better results in achieving a histological diagnosis of AIP than FNA [38]. Side-fenestrated needles appear to be less accurate in the diagnosis compared with front-cutting needles, such as Franseen and Fork-tip needles, which showed level 1 histology in approximately 56-72% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, new FNB needles have been developed to maintain tissue architecture in samples [37]. These needles showed better results in achieving a histological diagnosis of AIP than FNA [38]. Side-fenestrated needles appear to be less accurate in the diagnosis compared with front-cutting needles, such as Franseen and Fork-tip needles, which showed level 1 histology in approximately 56-72% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative results based on studies using newer FNB needles are still scarce. In fact, the Franseen and Fork-tip needles, characterized by a surface with multiple cutting points designed to provide improved control at the puncture site and stability at the tip allowing for enhanced penetration, showed very promising results in other abdominal masses [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. However, definitive assumptions of their comparative performance in the case of LN sampling cannot be drawn.…”
Section: Discussionmentioning
confidence: 99%
“…In the last years, a paradigm shift towards increased use of fine-needle biopsy (FNB) was observed in clinical practice [ 11 ]. The promising results observed with newer FNB needles, such as the Franseen needle (Acquire ® [Boston Scientific, Marlborough, MA, USA]) and the Fork-tip needle (SharkCore ® [Medtronic, Dublin, Ireland]), in tissue acquisition of pancreatic masses and of subepithelial lesions require confirmation also in the setting of LN biopsy [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews reported establishing the histological diagnosis of AIP using EUS-FNA and EUS-FNB. 30,31 Facciorusso et al compiled data on 631 cases in 15 reports with a diagnostic accuracy of 54.7% (95% confidence interval [CI] 40.9-68.4%) for the histologic diagnosis of AIP by EUS-FNB, which was significantly higher than the rate of 45.7% (95% CI 26.5-65%) reported using EUS-FNA. 30 Yoon et al compiled data on 440 cases from nine reports to determine an overall diagnostic accuracy of 87.2% (95% CI 68.8-98.1%) for the histologic diagnosis of AIP using EUS-FNB, which was significantly higher than the rate of 55.8% (95% CI 37.0-73.9%) reported for EUS-FNA.…”
Section: The Outcomes Of Eus-guided Pancreatic Sampling In the Diagno...mentioning
confidence: 99%
“…30,31 Facciorusso et al compiled data on 631 cases in 15 reports with a diagnostic accuracy of 54.7% (95% confidence interval [CI] 40.9-68.4%) for the histologic diagnosis of AIP by EUS-FNB, which was significantly higher than the rate of 45.7% (95% CI 26.5-65%) reported using EUS-FNA. 30 Yoon et al compiled data on 440 cases from nine reports to determine an overall diagnostic accuracy of 87.2% (95% CI 68.8-98.1%) for the histologic diagnosis of AIP using EUS-FNB, which was significantly higher than the rate of 55.8% (95% CI 37.0-73.9%) reported for EUS-FNA. 31 After collecting and analyzing data on 617 cases in 20 reports, Chhoda et al demonstrated that the rate of collecting a sufficient amount of tissue (FNB vs. FNA = 96.8% vs. 79.8%, P = 0.016) and accurate diagnosis rate (FNB vs. FNA = 60.20% vs. 42.02%, P < 0.0001) were superior using EUS-FNB.…”
Section: The Outcomes Of Eus-guided Pancreatic Sampling In the Diagno...mentioning
confidence: 99%